The Role of Job Satisfaction in Transitions into Self-Employment - Giuliano Guerra; Roberto Patuelli (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 2012)
As observed in many advanced economies experiencing an increase of self-employment rates since the late 1970s, a flourishing small- and medium-size enterprise sector is traditionally associated with positive economic development and growth. In the regional context, areas benefiting from an established entrepreneurial culture are in general more successful and innovative, as well as better equipped to sustain structural changes and to lessen unemployment. It is therefore important to investigate the reasons why individuals choose self-employment, and why they do it despite lower protection, higher risks, and possibly more effort than what is required in a comparable wage employment position. Existing research identifies better prospects of entrepreneurial earnings as compared to wages as a major stimulus towards selfemployment. However, besides pecuniary motivations, other factors may be considered when it comes to the occupational choice. These include displacement, uncertainty, (the threat of) unemployment, and (dis)satisfaction. Building on a job quits model, we propose a representation of transition behaviour from wage to self-employment which includes subjective evaluations of pecuniary and nonpecuniary satisfaction on the previous job. Individual microdata are drawn from the Swiss Household Panel (SHP), and cover the time period 1999–2008. Additionally, we focus on the dynamics of job satisfaction in order to highlight the role played by shocks in subjective evaluations, and introduce their interaction with levels to control for threshold effects.
Keywords: C25; J62; M13; 330